2004
DOI: 10.1016/j.bbamcr.2004.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin binds to and inhibits the activity of phosphoglycerate kinase

Abstract: Phosphoglycerate kinase (PGK) functions as a cytoplasmic ATP-generating glycolytic enzyme, a nuclear mediator in DNA replication and repair, a stimulator of Sendai virus transcription and an extracellular disulfide reductase in angiogenesis. Probing of a developmental expression library from Dictyostelium discoideum with radiolabelled calmodulin led to the isolation of a cDNA encoding a putative calmodulin-binding protein (DdPGK) with 68% sequence similarity to human PGK. Dictyostelium, rabbit and yeast PGKs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In the mammalian nucleus, Pgk1p influences DNA replication and repair and has been identified as a host factor necessary for in vitro mRNA synthesis of the Sendai virus (Ogino et al , 1999; Popanda et al , 1998). Dictyostelium , rabbit and yeast Pgkp can bind to calmodulin‐agarose in a calcium‐dependent manner, placing this protein in the realm of enzymes regulated by Ca 2+ /CaM‐mediated signalling (Myre and O'Day, 2004). In C. albicans it has been reported that, beyond the cytoplasm, Pgk1p is also located in the cell wall, although the function of the protein in this cellular compartment is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In the mammalian nucleus, Pgk1p influences DNA replication and repair and has been identified as a host factor necessary for in vitro mRNA synthesis of the Sendai virus (Ogino et al , 1999; Popanda et al , 1998). Dictyostelium , rabbit and yeast Pgkp can bind to calmodulin‐agarose in a calcium‐dependent manner, placing this protein in the realm of enzymes regulated by Ca 2+ /CaM‐mediated signalling (Myre and O'Day, 2004). In C. albicans it has been reported that, beyond the cytoplasm, Pgk1p is also located in the cell wall, although the function of the protein in this cellular compartment is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent probing of DNA expression libraries of Dictyostelium using CaMBOT led to the identification of many proteins not previously known to be CaMBPs including histone H1 (H1), phosphoglycerate kinase (PgkA) and thymidine kinase (TK1) and others [14]. Two other CaMBPs identified by CaMBOT-the nucleolar number regulator nucleomorphin (NumA) and the secreted, cysteine-rich matricellular protein (CyrA) have led to many other central discoveries including new binding partners, protein translocations and functions including the role of extracellular calmodulin [27][28][29][30][42][43][44]. A later CaMBP probing method utilized a glutathione-S-transferase (GST-CaM) fusion assay revealed DwwA, an IQ-like-motif protein required for scission in cytokinesis, similar to the human KIBRA [45].…”
Section: Detecting Calmodulin-binding Proteinsmentioning
confidence: 99%
“…A later CaMBP probing method utilized a glutathione-S-transferase (GST-CaM) fusion assay revealed DwwA, an IQ-like-motif protein required for scission in cytokinesis, similar to the human KIBRA [45]. More traditional approaches, CaM co-immunoprecipitation pulldown assays using anti-CaM antibodies or CaM conjugated agarose identified cyclin-dependent kinase 5 (Cdk5), a cytoplasmic and nuclear serine-threonine kinase with multiple transport and cell cycle roles; and the cell-cell adhesion molecule CadA [27,46,47].…”
Section: Detecting Calmodulin-binding Proteinsmentioning
confidence: 99%
“…Furthermore, proteins with additional regulatory domains associated with the PGK structure have been identified in several organisms including kinetoplastids as documented later in this review and various recent publications. The presence of some of these regulatory modules, such as the PAS-domain (Per-ARNT-Sim), calmodulin-binding domain (CaMBD), cyclic nucleotide binding domains (CNB) and transmembrane domains (TMD), possibly endow the PGK with non-canonical functions (table 3) [4,28,128]. An additional discussion of the possible implications of the presence of these regulatory domains in isoenzyme function will be discussed in the following sections.…”
Section: Pgk Functional Formsmentioning
confidence: 99%